Observation of enhanced ion particle transport in mixed H/D isotope plasmas on JET. (4th June 2018) - Maslov, M.; King, D.B.; Viezzer, E.; Keeling, D.L.; Giroud, C.; Tala, T.; Salmi, A.; Marin, M.; Citrin, J.; Bourdelle, C.; Solano, E.R.
Abstract: Particle transport in tokamak plasmas has been intensively studied in the past, particularly in relation to density peaking and the presence of anomalous inward particle convection in L- and H-modes. While in the L-mode case the presence of the anomalous inward pinch has previously been unambiguously demonstrated, particle transport in the H-mode was unclear. The main difficulty of such studies is that particle diffusion and convection could not be measured independently in steady-state conditions in the presence of a core particle flux. Therefore, it is usually not possible to separate the transport effect(inward convection), from the source effect (slow diffusion of particles introduced to the plasma core by neutral beam injection heating). In this work we describe experiments done on JET with mixtures of two hydrogenic isotopes: H and D. It is demonstrated that in the case of several ion species, convection and diffusion can be separated in a steady plasma without implementation of perturbative techniques such as gas puff modulation. Previous H-mode density peaking studies suggested that for this relatively high electron collisionality plasma scenario, the observed density gradient is mostly driven by particle source and low particle diffusivity D   <  0.5 * χ eff . Transport coefficients derived from observation of the isotope profiles in the new experiments far exceed that value—ion particle diffusion is found to be as high as D   ⩾  2 * χ eff, combined with a strong inward convection. Apparent disagreement with previous findings was explained by significantly faster transport of ion components with respect to the electrons, which could not be observed in a single main ion species plasma. This conclusion is confirmed by quasilinear gyrokinetic simulations.